Beyond the Observable: Conceptions and realizations of enacted multiliteracies in Ontario Social Studies Curriculum–One Multi-verse of Madness - Doyle-Jones, Carol; Loerts, Terry (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2024)
This research focuses on one teacher’s lived experience as he contributes towards a broader understanding of possibilities and constraints afforded by technologies, materials, and relationality during this recent shift in pandemic pedagogy. The pandemic drastically altered the way curriculum is enacted as there were shifts in the learning environment, the subject matter, and the way teachers and students engaged in literacy practices. To understand this shift, we explore: What are the participating teacher’s perceptions about how multiliteracies are utilized for classroom practice and pedagogy? How did this teacher’s pedagogy continue or change once the pandemic influenced curriculum enactment? This paper focuses on how one grade 6 teacher explored this pandemic pedagogical landscape in his classroom. This experience contributes to learning from the past, navigating the present, and continuing to shape the future of effective instruction in an elementary classroom.